Forest Waqf: An Alternative Solution for Protecting Environment in Kalimantan - Sukarni Sukarni; Firqah Annajiyah Mansyuroh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
This article provides an alternative solution in terms of environmental protection in Islamic law, namely a study of the description of the potential development of waqf law, in this case, forest waqf, as an alternative solution to environmental protection on the island of Kalimantan. The method used in this paper is normative juridical, which examines the law of ecological protection theoretically from the perspective of Islamic law and describes the possibility of new alternatives from the study of empowerment of waqf and its potential on the island of Kalimantan. The results show that waqf for the environment can balance development and environ-mental sustainability, as well as have an impact on sustainable environmental preservation, where future generations will have a level of utilization of the environment and natural resources that are at least equal to the level of utilization of the current generation, both in terms of the diversity of choices for natural resources, the quality of the environment and natural resources, and access to the environment and natural resources on the island of Kalimantan as the island where the capital city of Indonesia Archipelago is located.